Intention to Use Digital Finance MSMEs: The Impact of Financial Literacy and Financial Inclusion - Hermawan, Atang; Gunardi, Ardi; Sari, Lira Mustika (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
The purpose of this study is determine financial literacy affects intention to use digital finance and financial inclusion affects intention to use digital finance. Collecting data using questionnaires and PLS analysis method. The results show the intention to use digital finance is influenced by financial literacy with medium significance and financial inclusion with a very strong significance. This finding contributes for fintech knowledge, because the intention to use digital finance’s research is rare expecially for MSME actors, so this results provide suggestions for disseminating financial knowledge and services that have impact on usage intentions to end up with better market and MSME development. This research focuses on the intention to use digital finance for MSMEs, which is important because it requires adjustment to the times that lead to digitalization. The city of Bandung as a city with a fairly large number of MSMEs has attracted the attention of researchers Keywords: financial inclusion, financial literacy, intention to use digital finance